Do Job Demands affect Teachers’ Well-Being? A Meta-Analytical Review - Nurdinni Tilova; Andri Priadi (Journal of Global Business and Management Review, 2023)
The association between job demands and teachers' well-being was examined in a meta-analysis. We can accurately assess these relationships' magnitude by conducting a meta-analysis of these relationships. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), a systematic review was done, and data were gathered by recording research from multiple internet sources. From 2007 until 2022, these articles were released in UN Language. The essay, published in journals indexed in EBSCO and Emerald database, analyzes qualitatively, presents the data in sample size, standard deviation, and average, and addresses the relationship between job demands and teachers' well-being. For computing the average aggregate difference, creating a forest plot, and accounting for publication bias, the analysis employed JASP software. The findings showed a significant relationship (SE=0.23) between indicators of job demands and teachers' well-being. To increase the distinctive variance among the many tools used to evaluate job needs, we advise revisiting them.